Issues of Communicative Tolerance of University Teachers - Shoyimova Shokhista Sanakulovna (Researchparks Publishing, 2023)
This scientific article is devoted to the issues of communicative tolerance of teachers of higher educational institutions, and it is indicated that communicative tolerance is one of the main determinants of an effective educational process, as well as the main personal substructures that determine communicative tolerance.